Algal viruses hitchhiking on zooplankton across phytoplankton blooms - Frada, Miguel J (Commun Integr Biol, 2015)
Viruses infecting marine phytoplankton are key biogeochemical ‘engines’ of the oceans, regulating the dynamics of algal populations and the fate of their extensive blooms. In addition they are important ecological and evolutionary drivers of microbial diversification. Yet, little is known about mechanisms influencing viral dispersal in aquatic systems, enabling the rapid infection and demise of vast phytoplankton blooms. In a recent study we showed that migrating zooplankton as copepods that graze on marine phytoplankton can act as transmission vectors for algal viruses. We demonstrated that these grazers can concentrate virions through topical adsorption and by ingesting infected cells and then releasing back to the medium, via detachment or defecation, high viral titers that readily infect host populations. We proposed that this zooplankton-driven process can potentially boost viral dispersal over wide oceanic scales and enhance bloom termination. Here, we highlight key results and further discuss the ecological and evolutionary consequences of our findings.